An investigation of the effects of different text formats on middle school students’ reading comprehension performance - Betül Koparan (PLoS ONE, 2025)
This study is a quasi-experimental research that aims to compare the reading comprehension levels of students who read texts in textbooks through printed, digital, and augmented reality (AR)-supported formats. The sample of the study consisted of 150 students aged 11–12 who were enrolled in schools in Turkey. The participating students were randomly assigned to three equal groups (print, digital, augmented reality). During the data collection process, reading comprehension was assessed in five dimensions (literal comprehension, reorganization, inferential comprehension, evaluation, and appreciation) based on Barrett’s Taxonomy. In order to determine the students’ reading comprehension achievement levels, a “reading comprehension achievement test” was used. Initially, reading activities using the same printed texts were conducted with all three groups. Afterwards, a pre-test was administered. Following a five-week break, different reading activities were conducted with the three groups during the post-test phase. Intra-group comparisons of pre-test and post-test data were analyzed using the paired-samples t-test. ANCOVA analysis was used to test whether the differences in post-test reading comprehension scores between the groups were statistically significant. The results showed that the AR-supported reading activity improved students’ reading comprehension performance (p < .05, η2 = .388). The same trend was observed in all sub-dimensions of reading comprehension (literal comprehension p < .05, η2 = .140; reorganization p < .05, η2 = .217; inferential comprehension p < .05, η2 = .322; evaluation p < .05, η2 = .225; appreciation p < .05, η2 = .327). Therefore, it can be concluded that augmented reality books enhance the reading comprehension performance of children aged 11–12. On the other hand, there was no significant difference in reading comprehension performance between traditional reading and screen-based reading (p = .542). These findings indicate that AR content is more effective in improving students’ reading comprehension compared to printed and digital texts when reading storybooks. Consequently, the present research provides insights into the effects of different text formats on middle school students’ reading comprehension performance.